The Fiscal and Welfare Impacts of Reforming Fuel Subsidies in India - Anand, Rahul; Coady, David; Mohommad, Adil.; Thakoor, Vimal (Washington, D.C. : International Monetary Fund, 2013)
Rising fuel subsidies have contributed to fiscal pressures in India. A key policy concern regarding subsidy reform is the adverse welfare impact on households, in particular poor households. This paper evaluates the fiscal and welfare implications of fuel subsidy reform in India. Fuel subsidies are found to be badly targeted, with the richest ten percent of households receiving seven times more in benefits than the poorest ten percent. Although subsidy reform would generate substantial fiscal savings, the associated increases in fuel and other prices would lower household real incomes of all income groups. Better targeting of fuel subsidies would fully protect lower income households while still generating substantial net fiscal savings. Lessons from subsidy reforms in other countries are identified and discussed.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet